Impact of Peristalsis and Wall Properties on Diffusion in the Flow of a Chemically Responsive Jeffrey Fluid - Kiran, G. Ravi; Rajyalakshmi, K.; Ravindar, B. (Communications in Mathematics and Applications, 2022)
The hydrodynamic diffusion of a solute matter in the peristaltic flow of a chemically reactive incompressible Jeffrey fluid is studied as a model of fluid transport in the human intestinal system with wall properties. The long wavelength approximation, Taylor’s limiting condition and dynamic boundary conditions at the flexible walls are used to obtain the average effective dispersion coefficient in the presence of combined homogeneous and heterogeneous chemical reactions. The effects of various pertinent parameters on the effective dispersion coefficient are discussed. It is observed that average effective dispersion coefficient increases with amplitude ratio which implies that dispersion is more in the presence of peristalsis. Further, it also increases with the Jeffrey parameter and wall parameters. Conversely, dispersion is found to decreases with homogeneous and heterogeneous chemical reaction rates.
Keywords: Diffusion; Irreversible chemical response; Peristalsis; Jeffrey fluid; Fluid-structure interaction; Wall properties